PERMAINAN CARI KOTAK POIN (CARKOIN) SEBAGAI SARANA EDUKASI ANAK DALAM UPAYA PREVENTIF PENYAKIT DIARE DAN KECACINGAN - Nasichah, M.; Wantini, N.N.P. (Buletin Udayana Mengabdi; Vol 23 No 2 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i02.p13, 2023)
Children are the nation's next generation, therefore children need special attention in terms of education and health, so that they can become superior qualities for the progress of the nation. However, it should be noted that children have relatively weak immune systems, so they are susceptible to diseases such as diarrhea and intestinal worms. Factors causing diarrhea and intestinal worms are the lack of personal sanitation (clean and healthy living behavior) in children. The behavior in question is children defecating openly, playing with bare feet, not washing their hands before eating and after defecating, not keeping their fingernails and toenails clean, and eating snacks that are not kept clean. This educational game Find Points Box (CARKOIN) is made to increase children's knowledge and change children's behavior to be healthier. The implementation method in this activity is carried out through several stages. The results of the study showed that at each stage of implementation the children were enthusiastic about listening to the counseling material and were also enthusiastic about finding the point boxes and answering the questions in the boxes. Keywords: Diarrhea, Worms, Child, Education, Game.